2023
DOI: 10.1001/jamasurg.2022.6393
|View full text |Cite
|
Sign up to set email alerts
|

Zone 1 Endovascular Balloon Occlusion of the Aorta vs Resuscitative Thoracotomy for Patient Resuscitation After Severe Hemorrhagic Shock

Abstract: ImportanceAortic occlusion (AO) is a lifesaving therapy for the treatment of severe traumatic hemorrhagic shock; however, there remains controversy whether AO should be accomplished via resuscitative thoracotomy (RT) or via endovascular balloon occlusion of the aorta (REBOA) in zone 1.ObjectiveTo compare outcomes of AO via RT vs REBOA zone 1.Design, Setting, and ParticipantsThis was a comparative effectiveness research study using a multicenter registry of postinjury AO from October 2013 to September 2021. AO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…Increased time to AO with REBOA compared with RT was also described in a recent study of the AORTA registry 21 . In addition, 24-hour blood product transfusion was also greater with REBOA 22 . Besides time to AO, another factor which could have contributed to the difference in transfusions is the nature of the AO itself.…”
Section: Discussionmentioning
confidence: 58%
“…Increased time to AO with REBOA compared with RT was also described in a recent study of the AORTA registry 21 . In addition, 24-hour blood product transfusion was also greater with REBOA 22 . Besides time to AO, another factor which could have contributed to the difference in transfusions is the nature of the AO itself.…”
Section: Discussionmentioning
confidence: 58%
“…The balloon is inflated to occlude the aorta proximal to the presumed site of bleeding in the abdomen, pelvis, or both places. Multiple studies have suggested that REBOA does not worsen outcomes and, in many institutions and settings, improves outcomes with increased institutional experience . When REBOA is used in a setting with standardized training, protocol, expertise, and experience, outcomes are improved compared with patients who do not receive REBOA .…”
Section: Reboa Interventionmentioning
confidence: 99%
“…Resuscitative endovascular balloon occlusion of the aorta in zone 1 was associated with a statistically lower mortality compared with resuscitative thoracotomy, including all subgroup analysis. 39 Among patients with signs of life or presenting with traumatic cardiac arrest, prehospital and in-hospital data have shown promising results for NCTH control by REBOA. 40 Resuscitative endovascular balloon occlusion of the aorta represents a less invasive technique, allows personalized aortic occlusion (regarding injuries) and uninterrupted chest compressions.…”
Section: Reboamentioning
confidence: 99%